Gelatin–Alginat Koaservat Berstruktur Nano untuk Meningkatkan Stabilitas Minyak Sacha Inchi dalam Sistem Pangan - Yuszda K Salimi; Afrilia Ali; La Alio; Astin Lukum; Arviani Arviani (Jambura Journal of Chemistry, 2026)
Sacha inchi (Plukenetia volubilis L.) seed oil is rich in polyunsaturated fatty acids, such as alpha-linolenic acid (ω-3) and linoleic acid (ω-6), which are beneficial for health but are susceptible to oxidation. This study aimed to develop a stable and efficient microencapsulation system to protect oil from oxidative degradation using a complex coacervation method with gelatin and sodium alginate as coating materials, and calcium chloride (CaCl2, 2%) as a crosslinking agent. The process was carried out at pH 3.75, with homogenization at 12,000 rpm for 7 minutes, followed by low-temperature drying. Characterization included yield, encapsulation efficiency, moisture content, particle size, and the morphology of the microcapsules. The results showed a yield of 75.00 ± 2.10%, an encapsulation efficiency of 93.85 ± 0.93%, and a moisture content of 11.26 ± 1.37%. Dynamic Light Scattering-based Particle Size Analyzer analysis showed a hydrodynamic diameter of~0.100 µm (PDI 0.321) with good dispersion (88.4% transmittance). In the meantime, Scanning Electron Microscope observations revealed a spherical morphology with a smooth, crack-free surface. The gelatin-sodium alginate combination proved effective as a coating material, yielding microcapsules with high efficiency, good physical stability, and potential applications in functional food products and nutraceutical supplements.